Pengaruh Kompensasi Terhadap Honorer di Dinas Pendidikan Kota Makassar - Sari, Novi Indah; Hakim, Lukman; Nasrulhaq, Nasrulhaq (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
This study purposed to determine and analyze the effect of compensation on the performance of honorary staff in the Makassar city education office. This type of research was a descriptive study using quantitative methods and approaches that described compensation for the performance of honorary staff in the Makassar city education office. The population in this study was 157 people with a sample of 50 people. Then the analysis techniques used by researchers were descriptive statistical analysis techniques and simple linear regression analysis. The results of this study showed that compensation had a positive and significant effect on the performance of honorary staff, with an Adjusted R Square coefficient of 0.630 meaning that 63.0% of compensation affected the performance of honorary staff in the education office in Makassar.